Existence of solutions for fractional p-Kirchhoff type equations with a generalized Choquard nonlinearity - Chen, Wenjing (Topological Methods in Nonlinear Analysis, 2019)
In this article, we establish the existence of solutions to the fractional p-Kirchhoff type equations with a generalized Choquard nonlinearity without assuming the Ambrosetti-Rabinowitz condition.